He Impact of Self-Control on Students' Social Attitude at MTSN 1 Palangka Raya - Norhidayani, Norhidayani; Surawan, Surawan; Rahmida, Weni (Proceeding International Conference on Religion, Science and Education, 2025)
Self-control in each individual is very necessary so that he can direct himself when he wants to do something. This self-control must also be possessed by every student at school, especially during learning. Thus, as students who will bring change, it is hoped that they can distinguish between positive things and negative things, so that they can limit themselves and follow positive things that will have an impact on their social attitudes. This study aims to find out how the impact of self-control on students' social attitudes in MTsN 1 Palangka Raya City. This study uses a quantitative method, with the sample in this study is 72 students in grade VIII room 1-8 in MTsN 1 Palangka Raya City, in each class there are nine students as a sample, and the sample is taken by random sampling with a shuffle system. The data collection technique in this study uses a questionnaire of respondents and documentation, using a Likert scale with a range of 5, consisting of two statement items, namely positive and negative. Furthermore, the data analysis technique in this study uses a simple linear regression analysis model consisting of prerequisite tests (normality and linearity tests), hypothesis testing using t-tests., this study explains what is the effect of self-control on social attitudes in schools, how the impact of self-control on students' social attitudes, and includes the category of whether students' self-control in MTsN 1 Palangka Raya City.